Peran Perawat Komunitas Sebagai Edukator Terhadap Kesehatan Masyarakat Untuk Mencapai SDGs : Literatur Review - Ade Ilma Hasna; Miftahul Falah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Public health is a crucial element in achieving the Sustainable Development Goals (SDGs), particularly Goal 3, which emphasizes healthy lives and well-being for all. Achieving this goal requires the active participation of health workers at the community level, particularly community nurses, who serve as the spearhead of public health services. However, there are still limited studies assessing the effectiveness of nurses' educational role in supporting the success of the SDGs in the field. This study aims to analyze the role of community nurses as health educators in increasing community awareness, behavior, and independence towards achieving the SDGs. The method used was a literature review using the PRISMA guidelines through five stages of literature selection from the Garuda Portal and Google Scholar. Of the total 1,504 articles identified, four articles were selected based on inclusion criteria. The results showed that cadre training and education integration in primary care have been shown to improve community knowledge and adherence to healthy lifestyle behaviors. In conclusion, community nurses have a strategic role in strengthening sustainable health at the local level. It is recommended that further research develop longitudinal designs and utilize digital technology to expand the effectiveness of community-based health education.